Advances in biological wastewater treatment systems - Bui, Xuan-Thanh; Nguyen, Dinh Duc; Nguyen, Phuoc-Dan; Ngo, Huu Hao; Pandey, Ashok (Current developments in biotechnology and bioengineering, 2022)
Advances in Biological Wastewater Treatment Systems covers different recent advanced technologies, including green technologies, for biological wastewater treatment and wastewater reuse. The technologies involve novel biological processes and/or modified processes coupled with nano materials for improving the performance of the existing treatment processes. The book also describes treatment strategies for the current pollution from complex organic matter, nutrients, toxic substances, micro plastics and emerging micro pollutants in different water resources. The treatment processes describe the recent developed technologies for wastewater treatment and reuse such as biological nutrient removal, bioreactors, photobioreactors, membrane bioreactors, wetlands, algae-bacteria process, natural treatments, integrated/hybrid bio systems, etc. The novel bio systems include aerobic, anaerobic, facultative operation modes with various of types of microorganisms.